Identification of Key Drivers Influencing Housing-Led Regeneration in Urban Worn-Out Textures (Case Study: Damghan City) - Parsa Ahmadi Dehrashid; Saeed Zangane Shahraki; Ali Akbar Taghipour (مطالعات جغرافیایی مناطق خشک)
Aim: The aim of this study is to identify and explain the key drivers influencing Housing-Led Regeneration in the deteriorated urban fabric of Damghan. Emphasizing the necessity of intervention in the city’s inefficient and decaying neighborhoods, the study aims to focus on housing quality and its associated components to analyze the fundamental triggers for the successful realization of Housing-Led Regeneration. Given the central role of housing in the reproduction of urban space, a precise assessment of its influencing factors can contribute to more effective regeneration policymaking.Material & Method: Methodologically, the study adopts a mixed-methods and exploratory approach. The research population consists of 15 experts, specialists, and managers involved in urban regeneration, selected through purposive sampling. Data were collected using both structured and semi-structured questionnaires. Subsequently, cross-impact analysis was conducted using MicMac software to investigate causal relationships as well as the degree of influence and dependence among the variables.Finding: The findings indicate that the successful realization of Housing-Led Regeneration in Damghan’s deteriorated fabric depends on the simultaneous consideration of three critical factors: “land and housing prices”, “equitable distribution of resources and services”, and “human-centered transportation”.Conclusion: The results suggest that the success of Housing-Led Regeneration in Damghan requires a comprehensive, inclusive, and systemic perspective. This process will only yield desirable outcomes if planning goes beyond merely physical interventions to also address social, economic, and institutional dimensions. Furthermore, inter-organizational cooperation, public participation, and strengthening of institutional capacities at the local level are essential prerequisites for effective regeneration implementation.Innovation: The novelty of this research lies in its adoption of a holistic and systematic approach to analyzing the drivers influencing Housing-Led Regeneration. Unlike previous studies that tended to focus on isolated aspects, this research integrates economic, socio-cultural, spatial-physical, and environmental dimensions into a coherent framework, offering a more nuanced understanding of the dynamics underlying Housing-Led Regeneration.